Penerapan Metode Visualisasi Kolaborasi Aksi (ViKA) pada Pembelajaran Menyimak Teks Berita Kelas VIII (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
The learning method is an important part of the learning component. The selection of the right learning method can support the maximum achievement of learning objectives. Learning methods must continue to innovate so that it is not monotonous and boring for students. The Action Collaboration Visualization Method (ViKA) is one of the innovative and creative Indonesian language learning methods. The ViKA method is used in learning to listen to news texts for class VIII. The aims of this study are (1) to describe the Visualization of Collaborative Action (ViKA) method, (2) to describe the preparation for the application of the ViKA method in learning to listen to news texts for class VIII, (3) to describe the steps in applying the ViKA method in learning to listen to news texts for class VIII, (4) describe the advantages and disadvantages of the ViKA method. The method used in this research is descriptive qualitative. The main data source in this research is the ViKA learning method. The research instrument used was student worksheets related to news text elements. Data collection techniques using documentation techniques. This study uses descriptive data analysis techniques in the form of an explanation of the ViKA learning method. The subjects in this study were 15 grade VIII students. The results of this study indicate that there are differences in the results of student worksheets before and after the ViKA method is applied. Student worksheet results have increased after the ViKA method was applied. An abstract must be in English, consists of 150-250 words length, and contains at least: general theme of the article, focus, question, method, and general argument or main finding. Use this document as a template if you are using Microsoft Word 7.0 or later. Otherwise, use this document as an instruction set.